Proximate and Mineral Composition of Anabas Testudineus (Climbing Perch) in Peninsular Malaysia - Syakirah Hanim Mohd-Khairi, Nor; Arizal, Muslimatun; Hou Chew, Ha; Siew Ing, Nguang; Seng Chee, Poh; Ikhwanuddin, Mhd; Fay Komilus, Connie (International Journal of Engineering and Technology, 2018)
Anabas testudineus (Climbing Perch) is commonly eaten by Malaysians due to its tender flesh and tasty flavor. Usually, it is either freshly cooked or made into various dish including fermented fish called pekasam. This study was done to determine proximate composition, macromineral composition and micromineral composition in climbing perch from 3 states in Peninsular Malaysia. Fish with average body weight 73.18 g and total body length 15.93 m were sampled randomly from fish markets in Terengganu, Selangor and Perak. Proximate composition analysis was carried out using the AOAC method to assess the percentage (%) of protein, fat, moisture and ash. In addition, mineral composition analysis was conducted by using ICP-OES to study the concentration of Ca, P, Mg, Fe, Zn, Mn, Cu, and Cr in mg / kg in fish. Results from the analysis have been compared and analyzed using one-way ANOVA. The study found moisture content was the highest in Selangor (76.56 ± 0.44) % while ash and protein were higher in Perak`s fish (26.98 ± 0.21) % and (43.19 ± 0.81) % respectively. Terengganu`s fish contained the highest fat content at 17.19 ± 1.54 %. Perak`s fish demonstrated the highest macromineral content (Ca, P and Mg) which were 84336.87 ± 1525.41 mg/kg, 46843.90 ± 172.13 mg/kg and 1203.96 ± 10.45 mg/kg respectively. Perak`s fish also showed the highest content of micromineral (Fe and Cu) at (31.31 ± 0.09) mg/kg and (1.52 ± 0.00) mg/kg while Selangor`s fish showed the highest content of Zn and Mn (32.61 ± 0.64) mg/kg and (28.05 ± 0.57) mg/kg. In conclusion, climbing perch caught from Perak and Selangor might be good sources of macromineral and micromineral for human consumption.